2021
DOI: 10.1002/mame.202000696
|View full text |Cite
|
Sign up to set email alerts
|

Tri‐Layer Laminated Fabric‐Induced Sweating Surfaces for Passive Cooling

Abstract: Fabrics which can keep people cool in a hot climate have attracted considerable attention in recent years. Among various cooling strategies, fabric cooling by water evaporation is proved to be very safe, simple and sustainable. Here, a tri‐layer laminated fabric (TLF) inspired by perspiration is designed to realize passive cooling of human body. An interlayer fabric which is coated with crosslinked sodium polyacrylate can absorb and store a large amount of water. A moisture‐absorbing and quick‐drying fabric is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…The shortage of clean water resources is one of the major crises faced by human society. , The research and development of new methods for cheap, efficient, portable, and reliable access to clean water resources have attracted widespread attention both at industrial and individual levels. Solar energy is an inexhaustible source of clean energy with zero greenhouse gas emissions. Using abundant solar energy and seawater or other unpurified water to generate and collect freshwater through desalination and distillation is a practical and green approach. This technique has great potential to provide a solution to the growing challenge of water scarcity. …”
Section: Introductionmentioning
confidence: 99%
“…The shortage of clean water resources is one of the major crises faced by human society. , The research and development of new methods for cheap, efficient, portable, and reliable access to clean water resources have attracted widespread attention both at industrial and individual levels. Solar energy is an inexhaustible source of clean energy with zero greenhouse gas emissions. Using abundant solar energy and seawater or other unpurified water to generate and collect freshwater through desalination and distillation is a practical and green approach. This technique has great potential to provide a solution to the growing challenge of water scarcity. …”
Section: Introductionmentioning
confidence: 99%
“…Three‐layer laminated fabric (TLF) was designed with a moisture‐absorbing and quick‐drying fabric as the outer layer and an impregnated layer in the middle. [ 58 ] Sodium polyacrylate cotton with great water absorption potential taken as a high‐water absorption fabric that can absorb and store a large amount of water. The inner layer is a waterproof and breathable polyester knitted fabric coated with a thermoplastic polyurethane (TPU) fabric to ensure that the skin is dry when worn.…”
Section: Fibers and Textiles With Cooling Functionsmentioning
confidence: 99%
“…Reproduced with permission. [ 58 ] Copyright 2021, John Wiley and Sons. b) Schematics of comparison between NanoPE, normal PE, and cotton.…”
Section: Fibers and Textiles With Cooling Functionsmentioning
confidence: 99%
“…When compared to photonic structures, polymer‐based radiation cooling materials can not only reduce the cost but also greatly improve the extensibility and flexibility. At present, porous polymer materials, [ 8–11 ] aerogels, [ 12–14 ] coatings, [ 15–21 ] fabric, [ 22,23 ] nanostructured materials, [ 16,24–27 ] white cooler wood, [ 28 ] composite cooling materials, [ 11,29,30 ] and dielectric microsphere materials [ 31,32 ] have been widely studied. For example, Zhu et al.…”
Section: Introductionmentioning
confidence: 99%
“…When compared to photonic structures, polymer-based radiation cooling materials can not only reduce the cost but also greatly improve the extensibility and flexibility. At present, porous polymer materials, [8][9][10][11] aerogels, [12][13][14] coatings, [15][16][17][18][19][20][21] fabric, [22,23] nanostructured materials, [16,[24][25][26][27] white cooler wood, [28] composite cooling materials, [11,29,30] and dielectric microsphere materials [31,32] have been widely studied. For example, Zhu et al demonstrated a hierarchically designed nanofibre-based film, which allows for a high reflectivity of 96.3% in the 0.3-2.5 μm wavelength range and a selective emissivity of 78% in the 8-13 μm wavelength range.…”
Section: Introductionmentioning
confidence: 99%